(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Zakat has an important role in supporting social welfare, including in the health sector. This study discusses the optimization of zakat management through the National Zakat Agency (BAZNAS) to support sharia-based health social security. With the large potential of zakat in Indonesia, the utilization of zakat as funding for health services can help the poor access proper health insurance. This study uses a qualitative approach to analyze the policy, program implementation, and challenges faced in optimizing zakat in the health sector. The results show that BAZNAS has initiated various programs, such as BPJS Health contribution assistance, free health services, and medical cost subsidies for the poor. However, challenges in zakat distribution, transparency, and limited synergy with the government are still the main obstacles in the implementation of this program. Therefore, strategies to strengthen coordination between zakat institutions, government, and health institutions are needed so that zakat funds can be managed more effectively and sustainably in supporting an inclusive health social security system.